La ideología de la peregrinación - Spaccarelli, Thomas D. (Revista de Filología Románica, 2006)
MS. h.I.13 of El Escorial, sometimes called El libro de los huéspedes, presents an ideology of pilgrimage and guest/host theology based on the sojourn the risen Christ made with two disciples to Emaus. The ideology is founded on the principles of radical egalitarianism between social classes and sexes. The work was compiled to be read for the benefit of pilgrims on the Road to Santiago with reader/hearer participation being its real focus. Scenes from the stories of Santa María Madalena, Santa Marta and De vn cauallero Plaçidas (San Eustaçio) are analyzed to show how the elements of this doctrine are presented in the text.